Uma cosmopolita nos trópicos: a trajetória de Yvonne Jean no jornalismo carioca (1940-1950) - Teixeira, Ana Paula Tavares (2018)
Yvonne Jean came from Belgium to Brazil escaping the Nazi advance. She arrived in Rio de Janeiro in 1940, a city that was experiencing accelerated growth and urbanization. Here, the histologist of Jewish origin became a writer, journalist, translator, interpreter, gallery owner and cultural promoter. In the 1960s, she moved to the newly built federal district to work on the founding of the University of Brasilia (UnB) by the invitation of Darcy Ribeiro. Through the study of her life story, this research intends to illuminate the possibilities of intellectual women in the journalism of Rio de Janeiro, in the 1940s and 1950s. For this, I observe the circumstances of her coming to Brazil as well as her Jewish and European origin. Specifically, how those influenced on building her a relevant symbolic capital, as defined by Pierr Bourdieu. I also analyse her networks in Brazil, her involvement with leftist ideals and her personnal and professional choices in the 1950s, when major changes in the Rio press happened that led to the autonomization of the field of journalism in relation to the intellectual and political fields. In order to enrich the investigation, I bring in other life stories with common points and differences. This way, I hope to widen the spectrum of possibilities in analysis.